Deep blue emitting Cu(i) tripod complexes. Design of high quantum yield materials showing TADF-assisted phosphorescence. Issue 47 (22nd November 2018) - Schinabeck, Alexander; Rau, Nicholas; Klein, Marius; Sundermeyer, Jörg; Yersin, Hartmut
Abstract : Triplet and singlet harvesting in combination with enhancing the emitter rigidity leads to a landmark value of the photoluminescence quantum yield for dissolved Cu(i ) complexes. Abstract : In a previous investigation, it was shown that [Cu(tpym)(PPh3 )]PF6 1 with tpym = tris(2-pyridyl)methane represents a deep blue emitter ( λ max = 466 nm) though with a low emission quantum yield Φ PL if doped in a polymer (7%) or dissolved in a fluid solvent (≪1%). In this study, we present new tripod compounds with sterically demanding ligands: [Cu(tpym)(P( o -tol)3 )]PF6 2 and [Cu(tpym)(P( o -butyl-ph)3 )]PF6 3 with P( o -tol)3 = tris( ortho -tolyl)phosphine and P( o -butyl-ph)3 = tris( ortho-n -butylphenyl)phosphine. These compounds show high emission quantum yields even in a fluid solution (dichloromethane) reaching a benchmark value for3 of Φ PL = 76%. This becomes possible due to the specific design of rigidifying the complexes. Importantly, the deep blue emission color is maintained or even further blue shifted to λ max = 452 nm (compound3 powder). Compound2 is characterized photophysically in detail. In particular, it is shown that the lowest excited triplet state T1 experiences very efficient spin–orbit coupling (SOC). Accordingly, the phosphorescence decay rate is as large as 5 × 10 4 s −1 (20 μs) belonging to the fastest T1 → S0 transition values (shortest decay times) reported so far. Investigations down to T = 1.5 K reveal a large total zero-field splitting (ZFS) of 7 cm −1 (0.9 meV). Although thermally activated delayed fluorescence (TADF) grows in at T ≥ 160 K, the phosphorescence of2 still dominates (60%) over TADF (40%) at ambient temperature. Thus, the compound represents a singlet harvesting-plus-triplet harvesting material, if applied in an OLED.